2013
DOI: 10.1121/1.4773263
|View full text |Cite
|
Sign up to set email alerts
|

Wave motion on the surface of the human tympanic membrane: Holographic measurement and modeling analysis

Abstract: Sound-induced motions of the surface of the tympanic membrane (TM) were measured using stroboscopic holography in cadaveric human temporal bones at frequencies between 0.2 and 18 kHz. The results are consistent with the combination of standing-wave-like modal motions and traveling-wavelike motions on the TM surface. The holographic techniques also quantified sound-induced displacements of the umbo of the malleus, as well as volume velocity of the TM. These measurements were combined with sound-pressure measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
99
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 50 publications
15
99
1
Order By: Relevance
“…Recently, the full-field TM surface motion was measured using the multi-point LDV measurement (Fay et al 2005;Maftoon et al 2013), timeaverage Rosowski et al 2009) or stroboscopic holographic interferometry ; Del Socorro Hernandez-Montes et al, Cheng et al 2010Cheng et al , 2013Rosowski et al 2011), optical coherence tomography (Djalilian, et al 2008), and scanning laser Doppler vibrometry (Huber et al 2001). The experimental measurements demonstrated that the TM motion pattern was relatively simple with one area of maximal displacement at low frequencies (below 2,000 Hz) dominating.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the full-field TM surface motion was measured using the multi-point LDV measurement (Fay et al 2005;Maftoon et al 2013), timeaverage Rosowski et al 2009) or stroboscopic holographic interferometry ; Del Socorro Hernandez-Montes et al, Cheng et al 2010Cheng et al , 2013Rosowski et al 2011), optical coherence tomography (Djalilian, et al 2008), and scanning laser Doppler vibrometry (Huber et al 2001). The experimental measurements demonstrated that the TM motion pattern was relatively simple with one area of maximal displacement at low frequencies (below 2,000 Hz) dominating.…”
Section: Introductionmentioning
confidence: 99%
“…Certain mammalian middle ear models have considered the TyM to behave as a transmission line that causes a delay of approximately 40 μs [14]. However, it is unclear if direct physiological measurements of TyM motion are consistent with such a framework, as there is not always clear evidence for an inward-traveling wave carrying energy to the inner ear [2,3,8]. We note that the delays observed here for the bullfrog TyM are consistent with delays observed at the level of the inner ear [4,7] and are approximately an order of magnitude longer than those observed for mammalian middle ear delay for animals such as the gerbil.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral surface of the TM was then painted with a thin coat of zinc oxide (ZnO) suspended in distilled water at a concentration of 60 mg/cc to increase the light reflected from the surface. Such painting has been demonstrated to have little effect on the measured motion Cheng et al, 2013).…”
Section: A Preparation and The Use Of Human Temporal Bonesmentioning
confidence: 99%
“…The bones were either fresh or previously frozen at the time of preparation. The preparation of the temporal bones has been described previously (Cheng et al, 2010;Cheng et al, 2013;Cheng et al, 2015) and included (a) removal of the cartilaginous and most of the boney ear canal to expose over 90% of the lateral TM surface, (b) drilling out the mastoid and opening the facial recess to inspect the stapes and round window, and (c) opening the epitympanic space to view the malleus and incus head. After preparation, the bones were lightly fixed in Thiel solution (Thiel, 2002) for more than two weeks; this degree of fixation has been demonstrated to have only small effects on sound-induced stapes and umbo velocities (Stieger et al, 2012), and has been demonstrated to have little effect on the patterns of TM motion in treated human temporal bones (personal observation).…”
Section: A Preparation and The Use Of Human Temporal Bonesmentioning
confidence: 99%
See 1 more Smart Citation